Handgrip strength in medical students: Correlation with body mass index and hand dimensions - Al-Asadi, Jasim N (Asian Journal of Medical Sciences, 2018)
Background: Handgrip is a predictor of physical fitness, hand functions, and nutritional status. It is affected by many factors including age, sex, body mass index, and hand dimensions. Aims and Objectives: To assess the handgrip strength among medical students and to examine its correlation with body mass index and hand dimensions. Materials and Methods: This cross-sectional study included 256 students of both sexes selected from College of Medicine, Basrah University, Iraq using non-probability purposive sampling method. Their anthropometric parameters including height, weight, and hand dimensions were assessed using routine techniques. The handgrip was measured by using a handheld dynamometer. Hand preference was determined by asking which hand was used to write. Results: The mean age of the participants was 21.1 ± 1.9 years. The mean of handgrip strength was 34.1 ± 11.9 Kg. Males had significantly (P <0.001) greater handgrip strength than females. Statistically significant correlation was detected between body mass index, hand dimensions and handgrip strength. The right-handed students scored significantly higher grip strength with their preferred hand. While among left-handed students, no significant difference in handgrip strength was noticed between left and right hands. Multivariate logistic regression analysis showed that gender, hand span, height, and body mass index were independent determinants of handgrip strength. They accounted for 70.6% of the variation in handgrip strength. Conclusion: A significant effect of body mass index and hand span on handgrip strength among medical students was observed. Asian Journal of Medical Sciences Vol.9(1) 2018 21-26